2018
DOI: 10.9740/mhc.2018.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Surveys of substance use disorders education in US pharmacy programs

Abstract: Introduction:Substance use disorders (SUDs) are a significant US health problem affecting roughly 20 million Americans, but there continues to be limited access to SUD treatment and inadequate addiction medicine training. Therefore, it is important to understand how SUD education is being delivered to US health professionals, including pharmacists.Methods:A recent survey of US pharmacy programs' neuropsychiatry curricula was evaluated to identify any progress made toward increasing SUD education since the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…A 2015 survey on SUD content in US pharmacy programs revealed that most responding programs provided two hours of SUD in therapeutics, but fell short of the suggested content and hourly curricular recommendations from the American Association of Colleges of Pharmacy (AACP)'s Special Committee on SUD and Pharmacy Education. 9 Additionally, programs should meet the 2018 pharmacy core competencies for SUD education set forth by the Association for Multidisciplinary Education and Research in Substance Use and Addiction (AMERSA). 8 An SUD elective with an interactive-learning approach is one method of offering SUD content using a variety of teaching approaches as recommended by AACP and which also meets AMERSA's core competencies.…”
Section: Introductionmentioning
confidence: 99%
“…A 2015 survey on SUD content in US pharmacy programs revealed that most responding programs provided two hours of SUD in therapeutics, but fell short of the suggested content and hourly curricular recommendations from the American Association of Colleges of Pharmacy (AACP)'s Special Committee on SUD and Pharmacy Education. 9 Additionally, programs should meet the 2018 pharmacy core competencies for SUD education set forth by the Association for Multidisciplinary Education and Research in Substance Use and Addiction (AMERSA). 8 An SUD elective with an interactive-learning approach is one method of offering SUD content using a variety of teaching approaches as recommended by AACP and which also meets AMERSA's core competencies.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, while other U.S. colleges of pharmacy reported an average of 2.7 hours of required didactic instruction on SUD in 2015, The University of Texas at Austin College of Pharmacy curriculum provided 20 hours for 2021 PharmD graduates. 4 It may be reasonable to assume the impact of an APPE in addiction medicine would be even more profound for students with less prior exposure.…”
Section: Discussionmentioning
confidence: 99%
“…3 A 2015 survey of 75 AACP member schools found that 79% provided at least two hours of required didactic content related to SUD and 30% provided at least four hours. 4 However, advanced pharmacy practice experiences (APPEs) focused on SUD treatment were available in only 23% of programs and even then were offered to a mean of only 2.6 students each year. 5 The 2019 AACP environmental scan of opioid-related activities identified many new educational and service opportunities for students related to opioid overdose education and naloxone distribution.…”
Section: Introductionmentioning
confidence: 99%
“…A 2015 survey of US pharmacy programs found that 94% had curriculum addressing SUDs; however, the mean number of hours (2.7) was less than the 4 hours recommended by the American Association of Colleges of Pharmacy. 3 A 2017 survey 4 found that all medical schools that responded included content on pain and SUD, and a 2009 survey 5 of dental programs found that 73% addressed SUDs. Despite some health professional programs including SUD education in their curricula, students infrequently learn from a rigorous evidencebased SUD curriculum, [6][7][8] and the content likely varies across disciplines.…”
Section: Introductionmentioning
confidence: 99%